1975
DOI: 10.1139/v75-005
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Lycopodine. The Question of the Intermediacy of Piperidine-2-acetic Acid

Abstract: . 53, 41 (1375).In Lycopodirtm tristachyum lycopodine is derived from L-lysine whereas pipecolic acid is derived from D-lysine. Malonic acid serves as a specific precurser of the non-lysine derived segments of lycopodine. Pipendine-2-acetic acid is not incorporated into the alkaloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…As no differences were observed in retention time and in fragmentation pattern (Figure ), it could be concluded that the samples actually contained the esters of homopipecolic acid and homoproline. Homopipecolic acid was described before in Lycopodium species as an intermediate of the synthesis of Lycopodium alkaloids, while homoproline was isolated from Asteraceae species, as a precursor of pyrrolizidines, but their co‐occurrence has never been reported in plants and their biosynthetic origin is not known.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As no differences were observed in retention time and in fragmentation pattern (Figure ), it could be concluded that the samples actually contained the esters of homopipecolic acid and homoproline. Homopipecolic acid was described before in Lycopodium species as an intermediate of the synthesis of Lycopodium alkaloids, while homoproline was isolated from Asteraceae species, as a precursor of pyrrolizidines, but their co‐occurrence has never been reported in plants and their biosynthetic origin is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Homopipecolic acid was described before in Lycopodium species as an intermediate of the synthesis of Lycopodium alkaloids, 41,42 while homoproline was isolated from Asteraceae species, as a precursor of pyrrolizidines, 40 but their co-occurrence has never been reported in plants and their biosynthetic origin is not known.…”
Section: Identification Of Beta Amino Acid Derivativesmentioning
confidence: 99%
“…Through previous isotope labeling studies, 28,29 the Lycopodium alkaloids have been shown to be derived from L-lysine and malonyl-CoA (Figure 2a). Although biosynthetic hypotheses have been developed based upon these studies in addition to several others, 23 the underlying enzymes for the majority of Lycopodium alkaloid biosynthesis have not yet been elucidated.…”
Section: Case Study 1: Timing and Tissue Specificity Of Huperzine A Bmentioning
confidence: 99%
“…Several recent studies identified a type III polyketide synthase (PKS) and its corresponding gene in H. serrata [ 13 , 14 ]. A proposed biosynthesis pathway for the synthesis of Hup A and related lycopodium alkaloids consisting of pelletierine coupled with 4PAA was reported by Ma and Gang (2004) [ 4 ] based on previous studies [ 15 - 18 ]. Initially, L-lysine is decarboxylated by lysine decarboxylase to form cadaverine.…”
Section: Introductionmentioning
confidence: 99%